1999
DOI: 10.1002/hep.510300115
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study on a novel DNA virus (TT virus) infection and hepatocellular carcinoma

Abstract: We performed a case-control study to evaluate the association of a new human DNA virus named TT virus (TTV) with hepatocellular carcinoma (HCC). We recruited 174 subjects hospitalized for HCC (84% males; mean age: 64 years) and 118 patients hospitalized for non-liver diseases in Brescia, northern Italy, as controls (94% males; mean age: 66 years). TTV DNA was found in serum by polymerase chain reaction (PCR) in 26 cases (15%) and 11 controls (9.3%) (P G .1). TTV group 2 infection was identified in 16 cases (61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 27 publications
5
14
0
Order By: Relevance
“…Since the first isolation of TTV, most studies have shown that it might be relevant to liver disorders and liver damage and have a possible association with fulminant hepatitis, cryptogenic liver disease, non-A-G hepatitis, posttransfusion hepatitis, liver cirrhosis, and hepatocellular carcinoma (11,22,37,41,57,65). At the same time, epidemiological associations of TTV with B-cell lymphoma, Hodgkin's disease, aplastic anemia, idiopathic pulmonary fibrosis, acute respiratory disease, and autoimmune rheumatic disorders have also been described (6,16,29,30,32,52).…”
mentioning
confidence: 99%
“…Since the first isolation of TTV, most studies have shown that it might be relevant to liver disorders and liver damage and have a possible association with fulminant hepatitis, cryptogenic liver disease, non-A-G hepatitis, posttransfusion hepatitis, liver cirrhosis, and hepatocellular carcinoma (11,22,37,41,57,65). At the same time, epidemiological associations of TTV with B-cell lymphoma, Hodgkin's disease, aplastic anemia, idiopathic pulmonary fibrosis, acute respiratory disease, and autoimmune rheumatic disorders have also been described (6,16,29,30,32,52).…”
mentioning
confidence: 99%
“…Contrasting that, another group reported TTV-DNA to occur more frequently in patients with liver cirrhosis and HCC than in those with chronic hepatitis [27] . Using a case-control study to compare the prevalence of 174 Italian patients and matched controls, it was demonstrated that individuals infected with TTV did not exhibit an increased relative risk for developing HCC [90] . Furthermore, it has been demonstrated that the TTV genome is not found integrated into host hepatocyte DNA [91] , the one process that might represent a potential risk factor in the development of HCC.…”
Section: Ttv Infection In Liver Diseasesmentioning
confidence: 99%
“…Furthermore, retrospective analyses of patients treated with alpha interferon with or without ribavirin for underlying HCV infection have shown that therapy may result in a generally transient disappearance of detectable TTV from blood, especially if baseline TTV viremia is low, but that this is not accompanied by modulation of ALT levels unless HCV is also cleared (4,8,16,48). In addition, attempts to link TTV to hepatocellular carcinoma in patients positive or negative for HBV and HCV have given inconsistent results (107,132,156,184). Undoubtedly, the above observations rule out the notion that clinically evident liver disease is a frequent consequence of TTV infection.…”
Section: Clinical Significancementioning
confidence: 99%